Co-delivery of Dacarbazine and All-Trans Retinoic Acid (ATRA) Using Lipid Nanoformulations for Synergistic Antitumor Efficacy Against Malignant Melanoma - Chenyang Li; Xiuping Han (Nanoscale Research Letters, 2020)
Abstract Malignant melanoma is a highly aggressive skin cancer responsible for 80% of mortality, and the overall median survival in patients with metastatic melanoma is only 6–9 months. Combination treatment through the simultaneous administration of dual drugs in a single nanocarrier has been demonstrated to be elegant and effective in combatting cancer. Herein, we employ a combination therapy based on dacarbazine (DBZ), FDA approved drug for melanoma and all-trans retinoic acid (ATRA), promising anticancer agents loaded on lipid nanoformulations (RD-LNF) as a new treatment strategy for malignant melanoma. We have successfully encapsulated both the drugs in lipid nanoformulations and showed a controlled release of payload over time. We demonstrated that the simultaneous delivery of DBZ and ATRA could effectively reduce cell proliferation in a concentration-dependent manner. The combinational nanoparticles significantly reduced the colony formation ability of B16F10 melanoma cells. Flow cytometer analysis showed that RD-LNF induced a greater proportion of apoptosis cells with significant inhibition of cell cycle progression and cell migration. These results suggest the promising potential of RD-LNF in the treatment of malignant melanoma with high efficacy.